2021
DOI: 10.5539/gjhs.v13n9p100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Unintended Pregnancy among Women Receiving Antenatal Care Services: A Facility-Based Cross-Sectional Study in Ghana

Abstract: Globally, unintended pregnancy represents an important public health challenge with significant social, economic and clinical repercussions which are worse in low-income and middle-income countries. Appropriate use of modern contraceptives averts significant proportions of unintended pregnancies and pregnancy complications. The objective of this study was to determine the prevalence and determinants of unintended pregnancy and explore modern contraceptive use among pregnant women A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…On daily basis, the antenatal clinic takes care about 120 pregnant and postnatal women. This secondary analysis was part of a larger study that determined the prevalence of unintended pregnancy among women receiving antenatal care 18 . The study involved a face-to-face interview of women attending antenatal clinics based on a structured questionnaire between 1 st June and 31 st July, 2013.…”
Section: Study Design and Sitementioning
confidence: 99%
“…On daily basis, the antenatal clinic takes care about 120 pregnant and postnatal women. This secondary analysis was part of a larger study that determined the prevalence of unintended pregnancy among women receiving antenatal care 18 . The study involved a face-to-face interview of women attending antenatal clinics based on a structured questionnaire between 1 st June and 31 st July, 2013.…”
Section: Study Design and Sitementioning
confidence: 99%
“…Targeted interventions can contribute signi cantly to reducing unintended pregnancies and promoting the overall reproductive health and well-being of women. In a study in ghana, it was identi ed that only 28% of the couples use contraception among those 78.7% of women experiencing unintended pregnancies had never used contraceptives before their current pregnancies, highlighting a gap in the effectiveness of contraceptive methods (45). Conversely, our study revealed that, 28.7% of participants, were using contraceptives, out of which 61.9% of these participants had never used contraception before.…”
Section: Discussionmentioning
confidence: 48%
“…Conversely, our study revealed that, 28.7% of participants, were using contraceptives, out of which 61.9% of these participants had never used contraception before. The observed low prevalence of contraceptive use in our study could be attributed to various factors, such as couple doesn't know how to use, partnet did't want to use any contraception, a thought of occasional sex could't lead to pregnancy, not ready for pills or methods, newly married couples actively seeking conception, and concerns about potential side effects associated with contraceptive methods (45).…”
Section: Discussionmentioning
confidence: 62%